A randomised trial of nicotine assisted reduction to stop in pharmacies - the redpharm study - Taskila Taina; MacAskill Susan; Coleman Tim; Etter Jean-Francois; Patel Mahendra; Clarke Sarah; Bridson Rachel; Aveyard Paul (BMC, 2012)
Abstract Background Public policy and clinical treatment in tobacco addiction in the UK has focused on cessation: an abrupt attempt to stop all cigarettes. However, recent evidence suggests that allowing more gradual withdrawal from tobacco or even permanent partial substitution by nicotine replacement therapy (NRT) could lead to net benefits to public health. No jurisdiction has introduced smoking reduction programmes in normal clinical care and the best methods for their implementation is uncertain. Community pharmacists offering smoking cessation services in the UK are ideally placed to implement reduction programmes. This pilot study aims therefore to examine the feasibility of implementing smoking reduction programme in pharmacies, and also to see if behavioural support and a longer treatment affect the success rate for cessation. Design and methods This is a 2 × 2 randomised factorial trial of behavioural support versus no support and short versus standard length reduction programme. The pharmacists will recruit 16 patients per pharmacy, 160 smokers altogether. Pharmacists will randomise each participant by sealed envelopes. In a standard supported programme, the pharmacist will give support for 34 weeks, inviting participants to set a treatment goal and providing advice on how to reduce cigarette use. Participants in the short programme will be given the same advice on how to reduce but will reduce smoking over four weeks. Participants in the no support arms will be given a leaflet that describes the reduction programmes in 4-week and 34-week format. All participants are encouraged to use of NRT to support the reduction. These processes will be measured by recording the number of recruited smokers; percentage of those who reduce and sustain their consumption to at least 50% of baseline value, and the proportion of people who attain 4 weeks abstinence and 6 months abstinence. Interviews will assess smokers' and pharmacists' views on the way the programme ran. Discussion This is a pilot study to assess the feasibility of offering smoking reduction programme within pharmacies that offer naturalistic setting to show population benefit from these programmes. Findings from this trial will inform the development of evidence-based treatment for smokers who want to reduce and best approaches to engage reluctant quitters onto the programme. Trial Registration Current Controlled Trials ISRCTN 2010-019259-24